“Just A Minute Sweetheart, Mom’s Writing A Paper” Home, Flexible Learning, and Learning Biographies with Uneven Plots - Laura Servage (Adult Education Research Conference, 2007)
Explorations of “postmodern time,” the accelerating effects of technology, and long-standing challenges of work-life balance are presented to question the impacts of online study in the home on the learning experiences of working adults. The flexibility that makes online learning appealing may have unexplored costs and consequences for the quality of learning, and the quality of family life.